Extra-Neural Metastases From Primary Intracranial Ependymomas: A Systematic Review - Palmisciano, Paolo; Ferini, Gianluca; Barone, Fabio; Chavda, Vishal; Romano, Fabrizio; Amico, Paolo; Emmanuele, Donatella; Nicoletti, Giovanni F.; Pompili, Gianluca; Giammalva, Giuseppe Roberto; Maugeri, Rosario; Iacopino, Domenico Gerardo; et al. (Frontiers in Oncology, 2022)
Background Primary intracranial ependymomas (IE) are rare brain tumors rarely metastasizing outside the central nervous system. We systematically reviewed the literature on extra-neural metastases from primary IEs. Methods PubMed, Scopus, Web-of-Science, and Cochrane were searched following the PRISMA guidelines to include studies of extra-neural metastases from primary IEs. Clinical features, management strategies, and survival were analyzed. Results We collected 48 patients from 43 studies. Median age was 13 years (range, 2-65). Primary IEs were frequently located in the parietal (22.9%) and frontal (16.7%) lobes, and mostly treated with resection (95.8%) and/or radiotherapy (62.5%). Most IEs were of grade-III (79.1%), and few of grade-I (6.3%) or grade-II (14.6%). 45 patients experienced intracranial recurrences, mostly treated with resection (86.7%), radiotherapy (60%), and/or chemotherapy (24.4%). Median time-interval from primary IEs was 28 months (range, 0-140). Most extra-neural metastases were diagnosed at imaging (37.5%) or autopsy (35.4%). Extra-neural metastases were multifocal in 38 patients (79.1%), mostly involving cervical or hilar lymph-nodes (66.7%), lung/pleura (47.9%), and/or scalp (29.1%). Surgical resection (31.3%), chemotherapy (31.3%) and locoregional radiotherapy (18.8%) were the most common treatments for extra-neural metastases, but 28 (58.3%) patients were not treated. At last follow-up, 37 patients died with median overall-survivals from primary IEs of 36 months (range, 1-239), and from extra-neural metastases of 3 months (range, 0.1-36). Overall-survival was significantly longer in patients with grade-I and II IEs (P=0.040). Conclusion Extra-neural metastases from primary IEs are rare, but mostly occur at later disease stages. Multidisciplinary management strategies should be intended mostly for palliation.